Data from: Genome-wide support for incipient Tula orthohantavirus species within a single rodent host lineage ... - Labutin, Anton; Heckel, Gerald (Dryad, 2024)
Evolutionary divergence of viruses is most commonly driven by co-divergence with their hosts or through isolation of transmission after host-shifts. It remains mostly unknown, however, whether divergent phylogenetic clades within named virus species represent functionally equivalent byproducts of high evolutionary rates or rather incipient virus species. Here, we test these alternatives with genomic data from two widespread phylogenetic clades in Tula orthohantavirus (TULV) within a single evolutionary lineage of their natural rodent host, the common vole Microtus arvalis. We examined voles from 42 locations in the contact region between clades for TULV infection by RT-PCR. Sequencing yielded 23 TULV Central North and 21 TULV Central South genomes which differed by 14.9-18.5% at the nucleotide and 2.2-3.7% at the amino acid level without evidence of recombination or reassortment. Geographic cline analyses demonstrated an abrupt (<1 km wide) transition between the parapatric TULV clades in continuous ... : Genotyping of host nuclear DNA Genome-wide nuclear DNA (nucDNA) was used to infer the genetic structure of hosts via Genotyping by Sequencing (GBS) (Elshire et al., 2011). We sequenced at least five individuals per sampling site across the Central transect whenever possible, for a total of 200 individuals. Sequencing was carried out by LGC Biosearch Technologies (Berlin, Germany) using Illumina NovaSeq 6000 and PstI/MspI as restriction enzymes. We combined our dataset with GBS data of 216 additional individuals from the Porcelain transect (Saxenhofer et al., 2022) processed under the same conditions. This separate dataset consisted of voles from the Central and Eastern lineage as well as admixed individuals and served as a reference for the assignment of the newly genotyped 200 individuals to the evolutionary lineages. SNP calling was performed for all 416 individuals together using the GBS v2 pipeline (Tassel 5) (Glaubitz et al., 2014) with the M. arvalis genome (BioProject ID: PRJNA737461, Gouy et al., ...